The Three Flagellar Loci of Brucella ovis PA Are Dispensable for Virulence in Cellular Models and Mice - Sidhu-Muñoz, Rebeca S.; Tejedor, Carmen; Vizcaíno, Nieves (Frontiers in Veterinary Science, 2020)
Brucella ovis is a facultative intracellular bacterium that causes a non-zoonotic ovine brucellosis mainly characterized by male genital lesions and is responsible for important economic losses in sheep farming areas. Studies about the virulence mechanisms of Brucella have been mostly performed with smooth (bearing O-polysaccharide in lipopolysaccharide) zoonotic species, and those performed with B. ovis have revealed similarities but also relevant differences. Except for few strains recently isolated from unconventional hosts, Brucella species are non-motile but contain the genes required to assemble a flagellum, which are organized in three main loci of about 18.5 kb, 6.4 kb and 7.8 kb. Although these loci contain different pseudogenes depending on the non-motile Brucella species, smooth B. melitensis 16M builds a sheathed flagellum under particular culture conditions and requires flagellar genes for virulence. However, nothing is known in this respect regarding other Brucella strains. In this work, we have constructed a panel of B. ovis PA mutants defective in one, two or the three flagellar loci in order to assess their role in virulence of this rough (lacking O-polysaccharide) Brucella species. No relevant differences in growth, outer membrane-related properties or intracellular behavior in cellular models were observed between flagellar mutants and the parental strain, which is in accordance with previous results with B. melitensis 16M single-gene mutants. However, contrary to these B. melitensis mutants, unable to establish a chronic infection in mice, removal of the three flagellar loci in B. ovis did not affect virulence in the mouse model. These results evidence new relevant differences between B. ovis and B. melitensis, two species highly homologous at the DNA level and that cause ovine brucellosis, but that exhibit differences in the zoonotic potential, pathogenicity and tissue tropism.